The Effect Of Tea And Spent Tea Towards Digestion Properties And Development Of Low Glycemic Index Biscuit - Ismail, Nurul Nadiah (2018)
Tea (Camellia sinensis L.) is one of native plants which is rich in phenolic compounds and antioxidant elements, widely recognized for its benefits for human consumption. However, the informarion on chemical characteristics of the tea and residual tea leaves originated from the by-product of tea beverage manufactures is still insufficient. Therefore, this study aimed to evaluate the hypoglycemic effect of antioxidant activity which is present in tea leaves, as one of food ingredients in production of low glycemic food product.